Force Sensing by Piezo Channels in Cardiovascular Health and Disease. Issue 11 (November 2019) - Beech, David J.; Kalli, Antreas C.
Abstract : Mechanical forces are fundamental in cardiovascular biology, and deciphering the mechanisms by which they act remains a testing frontier in cardiovascular research. Here, we raise awareness of 2 recently discovered proteins, Piezo1 and Piezo2, which assemble as transmembrane triskelions to combine exquisite force sensing with regulated calcium influx. There is emerging evidence for their importance in endothelial shear stress sensing and secretion, NO generation, vascular tone, angiogenesis, atherosclerosis, vascular permeability and remodeling, blood pressure regulation, insulin sensitivity, exercise performance, and baroreceptor reflex, and there are early suggestions of relevance to cardiac fibroblasts and myocytes. Human genetic analysis points to significance in lymphatic disease, anemia, varicose veins, and potentially heart failure, hypertension, aneurysms, and stroke. These channels appear to be versatile force sensors, used creatively to inform various force-sensing situations. We discuss emergent concepts and controversies and suggest that the potential for new important understanding is substantial.